Fatherless analysis of children’s development social-emotional - Diya Fatihah Zahra; Syarifah Zafira Zain; Ime Nur Azzahra; Aulia Az Zahra; Adharina Dian Pertiwi (Kepompong Children Centre Journal, 2023)
Fatherless is a circumstance Where an individual must live Far from his father. This happens when somebody loses the presence and influence of an excellent father's physique or emotions. Minimal This father figure can be caused by various factors, including divorce, death, and parents who do it. Long Distance Marriage: Work causes an individual to lose the impact of a good father figure. Social-emotional development involves emotions, thoughts, and behavior involving a child's ability to engage with their environment, such as friends, peers, adults, etc. This allows them to adapt effectively to hope, community, and nation. This research aims to analyze the development of social-emotional children who are fatherless in life and facilitate readers so that they can increase their understanding of the stages of development of an emotional child who is in a fatherless condition. Data analysis was conducted via technique interview by taking five samples from 3 sources. The results of this study conclude that from 5 samples with three different fatherless characteristics, development socially. The child's emotions are pretty stable in the case of a fatherless long-distance marriage.